Pragmatic Constraints on Syntactic Structures: A Study of Contextual Meaning in English Language Use - Adinda Dea Nazhira; Nabila Zuhairya; Laila Anum; Gadis Anggun Fitrah; Siregar, Deasy Yunita (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This study investigates the interplay between pragmatic constraints and syntactic structures in the English language, emphasizing how context influences language use. Through a qualitative literature review, the research highlights the significant role of pragmatic considerations in shaping syntactic choices. Key findings reveal that speakers modify their syntactic structures to fulfill communicative goals, manage politeness, and emphasize information based on contextual cues. Furthermore, the analysis examines cross-linguistic perspectives, demonstrating the variability of these influences across different languages. The implications of these findings extend to language education, second language acquisition, and computational linguistics. The study concludes with suggestions for future research into the evolving dynamics of syntax and pragmatics in digital communication.   Keywords:Pragmatics, Syntax, English Language, Contextual Meaning, Language Use, Politeness, Cross-linguistic Perspectives, Language Education.